Global Society Impact on Students’ Career Development - Mufrihah, Arina; Suherman, Uman; Budiamin, Amin (Indonesian Journal of Guidance and Counseling: Theory and Application, 2023)
Abstrak Dampak masyarakat global terhadap perkembangan karir individu adalah nyata tak terhindarkan. Ekonomi global pun menuntut individu untuk secara berkelanjutan menyesuaikan dirinya dengan tuntutan perubahan, mempelajari keterampilan-keterampilan abad 21, dan pengembangan karir berbasis belajar sepanjang hayat. Karena itu, bimbingan dan konseling karir juga harus mengusung visi belajar sepanjang hayat untuk menyepadankan dengan perubahan persyaratan dunia kerja yang dihadapi siswa. Asesmen karir tidak sebatas mengungkap potensi dan kekuatan siswa, lebih jauh membantu siswa meningkatakn pemahaman kehidupan karir dan membuat keputusan-keputusan. Dalam dunia kerja abad 21 yang didasari pada ekonomi pengetahuan, berbagai isu tentang tenaga kerja yang beragam serta potensi terjadinya marginalisasi dan diskriminasi di dunia kerja juga menjadi fokus dan perhatian dari layanan bimbingan dan konseling karir. Abstract The impact of global society on individual career development is unavoidable. The global economy also requires individuals to sustainably adapt themselves to changing demands, learn 21st century skills, and develop career life based on lifelong learning. Therefore, career guidance and counseling must also promote the vision of lifelong learning to match the changing requirements of the world of work faced by students. Career assessment is not limited to revealing the students’ potential and strengths, it also helps students increase their understanding of career life and make decisions. The world of work in the 21st century which is based on the knowledge economy, various issues regarding a diverse workforce and the potential for marginalization and discrimination are also the focus and attention of career guidance and counseling services.